2001
DOI: 10.1006/viro.2001.1079
|View full text |Cite
|
Sign up to set email alerts
|

Extensively Deleted Simian Immunodeficiency Virus (SIV) DNA in Macaques Inoculated with Supercoiled Plasmid DNA Encoding Full-Length SIVmac239

Abstract: Using long-distance DNA PCR, we prospectively followed rhesus monkeys that had been inoculated intramuscularly with supercoiled plasmid DNA encoding intact simian immunodeficiency virus (SIV). From 4 to 10 weeks postinoculation onward, we detected extensively deleted proviral genomes along with full-length viral genomes in peripheral blood mononuclear cells (PBMC) in adult macaques. During their chronic asymptomatic phase of infection, the frequency of deleted proviral genomes was similar in PBMC and lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Previous studies have shown that inoculation of animals with plasmids encoding a full‐length proviral genome can establish a persistent viral infection [6–8, 10–13, 18, 19, 21]. This study demonstrates that inoculation with a plasmid encoding the proviral genome for SHIV 89.6 produces a persistent viral infection in rhesus macaques.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have shown that inoculation of animals with plasmids encoding a full‐length proviral genome can establish a persistent viral infection [6–8, 10–13, 18, 19, 21]. This study demonstrates that inoculation with a plasmid encoding the proviral genome for SHIV 89.6 produces a persistent viral infection in rhesus macaques.…”
Section: Discussionsupporting
confidence: 52%
“…Despite these concerns, identifying the mechanisms by which attenuated vaccines confer protection is an area of considerable interest. It has been shown previously that cats, goats, and monkeys inoculated with plasmids encoding full‐length lentivirus proviral genomes develop persistent viral infections [6–8, 11, 12, 18, 19, 21]. Based on these studies the use of full‐length lentivirus proviral plasmids as a method for live attenuated vaccine delivery is being considered [10, 13].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that most of the proviral DNA in resting CD4 ϩ T cells in peripheral blood of infected patients either carries intrinsic defects precluding expression of the HIV genome or is subjected to an epigenetic control mechanism. Pion et al (35,36) and Sanchez et al (37) have previously demonstrated a high proportion of truncated proviruses in PBMC and lymph nodes of HIV-1-infected individuals and simian immunodeficiency virus-infected macaques but not in in vitro-infected CD4 ϩ T cells. Thus, the absence of selective mechanisms leading to the accumulation of defective and expression-blocked proviruses in vivo can cause the great majority of proviruses in in vitro HIV-1-infected CD4 ϩ T cells to be reactivated by prostratin or PHA.…”
Section: Discussionmentioning
confidence: 97%
“…The immunized macaques showed SIV viral blips at early timepoints, but these became infrequent over time [28]. The instability of proviral sequences as well as the low fraction of full-length proviral DNA was also shown for SIV by Pion et al [29]. These authors inoculated purified, supercoiled SIVmac239 plasmid DNA intramuscularly into rhesus macaques, which resulted in high levels of viremia.…”
Section: Discussionmentioning
confidence: 82%